2016
DOI: 10.1002/2015wr017725
|View full text |Cite
|
Sign up to set email alerts
|

Movements of the thermocline lead to high variability in benthic mixing in the nearshore of a large lake

Abstract: The thermocline of Lake Ontario is in constant motion, and as it washes back and forth along the sloping lakebed there is a striking asymmetry in near‐bed stratification and benthic turbulence between its rise and fall. Detailed field observations of the stratification and water currents from the summers of 2012 and 2013 showed that the thermocline motions had large amplitudes (as high as 15 m) and a dominant period between 16 and 17.5 h, corresponding to a near‐inertial internal Poincaré wave. During the fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 83 publications
(162 reference statements)
0
18
0
Order By: Relevance
“…In Lake Ontario, seiche-induced vertical thermocline deflections of up to 15 m have been observed, which resulted in diffusivities varying by a factor of 500. This occurred synchronously to the remarkable asymmetry in near-bed stratification, which oscillated between instability and ∼1 K m −1 (Chowdhury et al 2016). Although the details differ with the depth, slope, temperature (larger α for warmer water), and type of basin-scale waves, the common asymmetry in BBL stratification and turbulence is directly related to upslope and downslope flows, as shown in situ (Lorke et al 2008, Cossu & Wells 2013 and for models , Lorrai et al 2011.…”
Section: Shear-induced Convection Over Slopesmentioning
confidence: 72%
See 1 more Smart Citation
“…In Lake Ontario, seiche-induced vertical thermocline deflections of up to 15 m have been observed, which resulted in diffusivities varying by a factor of 500. This occurred synchronously to the remarkable asymmetry in near-bed stratification, which oscillated between instability and ∼1 K m −1 (Chowdhury et al 2016). Although the details differ with the depth, slope, temperature (larger α for warmer water), and type of basin-scale waves, the common asymmetry in BBL stratification and turbulence is directly related to upslope and downslope flows, as shown in situ (Lorke et al 2008, Cossu & Wells 2013 and for models , Lorrai et al 2011.…”
Section: Shear-induced Convection Over Slopesmentioning
confidence: 72%
“…Model results indicate that convective turbulence during upflow inefficiently mixes already homogenized BBL water. During the strongly stratified downflow phase, BBL turbulence is suppressed (Chowdhury et al 2016). Hence, the question remains how efficiently the BBL water exchanges with interior water to store the potential energy generated by BBL turbulence , Lorrai et al 2011.…”
Section: Shear-induced Convection Over Slopesmentioning
confidence: 99%
“…During the upslope current, cold deep water flows over the warmer sediments. The resulting intermittent instability drives free convection and accelerates the fluxes at the sediment-water interface by more than 1 order of magnitude, as experimentally observed by Kirillin et al (2009), Lorke et al (2005) and Chowdhury et al (2016). In lakes with anoxic water layers, the seiche-induced oscillations can be accompanied by periodical changes in the oxygen concentration in a large internal shoreline area as described by Deemer et al (2015) for Lacamas Lake.…”
Section: Introductionmentioning
confidence: 72%
“…Wind‐induced large amplitude internal waves are a ubiquitous feature of large thermally stratified lakes, and the resulting oscillating baroclinic flows have the potential to pump waters in and out of coastal embayments that have depths greater than the thermocline. For example, typical internal wave amplitudes are of order 10 m with periods of 1–2 d in most of the Great Lakes (Rao and Murthy ; Bouffard et al ; Austin ; Chowdhury et al ) and amplitudes of 5–10 m are observed in Lake Simcoe (Chowdhury et al ; Cossu et al ). In particular, a number of studies in long, deep, stratified lakes have discussed the importance of internal seiche pumping in the lateral transport of dissolved oxygen (DO) and suspended sediments (Lawrence et al ; Laval et al ; Valipour et al ).…”
mentioning
confidence: 99%